Digital Literacy Skills and Cybercrime Preparedness Among Higher Education Students: A Belshaw Framework Approach - Arin Prajawinanti; Nurul Setyawati Handayani; Dewi Alifatul Wasi'ah; Indah Novitasari (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2026)
Background of the study: Students are active digital technology users, making them highly vulnerable to hacking, phishing, and digital crime, which highlights the urgent need for digital literacy to protect against cybercrime. Purpose: This study examines the digital literacy levels of students at UIN Sayyid Ali Rahmatullah Tulungagung, the factors affecting it, and strategies to mitigate cybercrime risks. Method: An Exploratory Sequential Mixed Methods design was adopted. Quantitative data was gathered from 393 respondents via stratified random sampling using a 30-item Likert questionnaire, analyzed using simple linear regression. Qualitative data originated from semi-structured interviews with five purposively sampled informants, followed by thematic analysis and source triangulation. Findings: Overall digital literacy scored 88%, highest in cultural competence (96%) and lowest in creative production (75%). Cybercrime anticipation averaged 88%, yet 20-25% of students neglected technical safeguards like antivirus and two-factor authentication. Regression analysis (β = 0.653, t = 19.986, F = 399.454, R^2 = 0.506, p < .001) confirmed digital literacy significantly predicts cybercrime preparedness. Qualitative analysis identified additional determinants: emotional self-regulation under threat and engagement with safety content. Conclusion: Digital literacy exerts a meaningful influence on student readiness to counter cybercrime. Nonetheless, deficits in technical security habits indicate competence-based measures alone are insufficient. Institutions are urged to embed continuous digital safety education across the curriculum.